Reviews / Comptes rendus (Food & History, 2013)
Abstract Cynthia SHAFER-ELLIOTT, Food in Ancient Judah: domestic cooking in the time of the Hebrew Bible (Equinox / Acumen: Sheffield, 2013) 256 pp; 10 figs; price £60/99.95; ISBN 978-1-908049-73-5. Ken ALBALA and Trudy EDEN (eds), Food and Faith in Christian Culture. New York: Columbia University Press, 2011. 265 pp. ISBN: 9780231149976. Philip SLAVIN, Bread and Ale for the Brethren: The Provisioning of Norwich Cathedral Priory, 1260‑1536. Studies in Regional and Local History 11 (University of Hertfordshire Press, Hatfield, 2012) xvii+220 pages, 18 figs, hb £35, pb £18.99. ISBN 978-1-907396-63-2. Joan FITZPATRICK (ed.), Renaissance Food from Rabelais to Shakespeare (Farnham, Ashgate, 2010), 171 pages. ISBN 9780754664277; Price: 99. Rebecca EARLE, The Body of the Conquistador: Food, Race and the Colonial Experience in Spanish America (Cambridge, Cambridge University Press, 2012), 265 pages, 21 illustrations. Price: £60.00 (99.00). ISBN 978-1-107-00342-2. Matthieu LECOUTRE, Ivresse et ivrognerie dans la France moderne (Rennes, Presses universitaires de Renne / Tours, Presses universitaires François- Rabelais de Tours, 2011), 395 pages, 20 black and white illus., 8 colour illus. Price : €21. ISBN 978-2-7535-1706-6. Philippe MEYZIE, L’alimentation en Europe à l’époque moderne. Manger et boire, XVIe s.-XIXe (Paris, Armand Colin, “Collection U: Histoire”, 2010), 288 pages. ISBN 9782200244071. Rachel RICH, Bourgeois consumption. Food, space and identity in London and Paris, 1850-1914 (Manchester University Press, Manchester, 2011), 239 pages, 8 figures, 2 tables. Price : £55. ISBN 978 0 7190 8112 5. Kilien STENGEL, L’aide alimentaire : colis de vivres et repas philanthropiques. Histoire de la Gigouillette 1934-2009 (L’Harmattan, coll. “Historiques”, 2012), 140 pages. ISBN : 978-2-296-296776-2 ; Prix : €14,50. Yang JISHENG, Tombstone: The Great Chinese Famine, 1958-1962 (London, Allen Lane, 2012), 629 pages, 1 illustration. Price : £30. ISBN 978-1-846-14518-6. ; Zhou XUN (ed.), The Great Famine in China, 1958-1962: A Documentary History, Yale University Press, New Haven, Connecticut, 2012, 204 pages, 1 illustration, ISBN 978-0-300-17518-9. América Solanger BUSTAMENTE ARÉVALO, Ernährungserziehung (shokuiku) und die nationale Identität Japans [Food Education (shokuiku) and National Identity in Japan], (München, Iudicium 2013), 159 pages, 6 illustrations. ISBN 978-3-86205-307-0 (published in German); price : € 18. Dorothy DUNCAN, Canadians at Table: A Culinary History of Canada (Toronto, Dundurn, 2011), 248 pages, illustrated. ISBN 9781459700383; price: C24.99; Barbara SANTICH, Bold Palates: Australia’s Gastronomic Heritage, Kent Town, South Australia: Wakefield Press, 2012, 336 pages, illustrated, AU49.95, ISBN 9781743050941. Jeffrey M. PILCHER, Planet Taco. A Global History of Mexican Food (New York, NY, Oxford University Press, 2012), 292 pages, 44 images. ISBN 978-0-19-974006-2; price: US 27.95.